EXPLORING THE HISTORY OF RELIGIOUS MODERATION AS A PILLAR OF PEACE EDUCATION IN MINAHASA - Meily Meiny Wagiu; David Rade Manat Simanjuntak; Ryanto Adilang; Andries Kango; Englin R. Manua (Balai Penelitian dan Pengembangan Agama Makassar, 2026)
This research aims to explore the historical development of religious moderation within the cultural context of Minahasa and to analyze its relevance as a foundation for peace education in the contemporary era. Although studies on religious moderation in Indonesia has significantly increased, most studies remain macro-oriented and lack in-depth integration between local cultural values and contextual educational strategies. This gap highlights the need for a more grounded and culturally embedded analysis. This research employs a qualitative approach through a systematic literature review, supported by thematic analysis and historical interpretation, to examine the evolution and transformation of moderation values in Minahasa society. The findings reveal that religious moderation in Minahasa is not a fixed cultural trait, but a socially constructed and continuously negotiated process shaped by local wisdom such as Mapalus (mutual cooperation), customary deliberation, and the Toar Lumimuut narrative, which embodies equality and social solidarity. However, these values are increasingly challenged by digital radicalization, misinformation, and the weakening of intergenerational transmission. This research argues that integrating religious moderation into peace education requires adaptive, critical, and context-sensitive strategies, particularly through digital engagement and culturally grounded curricula. The research contributes to the existing literature by offering a contextualized conceptual framework that positions local wisdom as a dynamic resource for strengthening peace education and sustaining social harmony in a rapidly changing society.